Ensino de matemática: significados construídos em contexto Akwẽ-Xerente - Lima, Simone Maria Alves de (2024)
Based on Cultural-Historical Theory, this research seeks to analyze how the object of knowledge "monetary system" is signified in mathematics teaching by Akwẽ-Xerente teachers. Its field of investigation is maths teaching in 5th grade primary school classes in schools of the Akwẽ-Xerente ethnic group. This is a qualitative study with field research as its methodological support. Data was collected through documents and interviews and seeks to uncover the meaning of teaching the object of knowledge monetary system in maths teaching and answer questions relating to the conditions and forms, production, selection and use of teaching materials from the perspective of differentiated education. The sections follow the specific objectives, which are to present the theoretical categories "culture" and "meaning" and their relationship with maths teaching and the process of building indigenous school education in Brazil and the Akwẽ-Xerente people. The methodological section provides details of the work plan, as well as the data generation process and the a posteriori constitution of the thematic categorical analysis units: 1) Monetary system: meanings in maths teaching and 2) Contradictions: monetary system. The analyses were supported by the content analysis technique using the Iramuteq software. The results showed that the teaching of the knowledge object 'monetary system' is based on the need for appropriation and aims to prepare the new generations for buying and selling and banking relations, as well as for the defence of the Xerente lands and culture. However, the lack of specific teaching materials means that teachers and students are faced with school maths terms that have no meaning in Akwẽ culture, which requires translations and leads to the insertion of new words and changes in meaning. In an attempt to avoid such changes, the Akwẽ teachers, in contradictory movements, select the objects of knowledge that meet the needs of the ethnic group and adapt them to the meanings of the Xerente culture: they start teaching maths using the Xerente numbering system and continue with the decimal numbering system, the necessary basis for appropriating knowledge of the monetary system; they use writing, but resort to orality, maintaining the Xerente way of teaching and learning; they align Western knowledge with the meanings and values of the Akwẽ-Xerente culture, maintaining the intentionality of teaching. However, this is a responsibility that cannot be taken on by indigenous teachers alone; it calls for investment and involvement from the education system. After all, access to knowledge about the monetary system does not mean absorbing capitalist forms of profit and advantage. On the contrary, it highlights the need for investment in favourable conditions for teaching that provides the opportunity to appropriate this knowledge, but legitimised in the meanings and values of the Akwẽ culture of use and economy. In conclusion, given this reality, there is an urgent need to comply with the proposal for specific, differentiated, intercultural and bilingual school education, especially regarding the production of specific materials, the organization of the curriculum and teaching times and spaces.